2014
DOI: 10.1039/c4ra02827a
|View full text |Cite
|
Sign up to set email alerts
|

The efficient hydroxyalkylation of phenol with formaldehyde to bisphenol F over a thermoregulated phase-separable reaction system containing a water-soluble Brønsted acidic ionic liquid

Abstract: A temperature-dependent biphasic system of IL–phenol–water was applied in the hydroxyalkylation of phenol with formaldehyde to bisphenol F. [C6MIM][HSO4] gave high yield of 80.5% and selectivity of 96.9% for bisphenol F. The recovered [C6MIM][HSO4] retained the original activity after six recycling-uses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…However, these homogeneous catalysts have several drawbacks such as toxic waste, equipment corrosion, hazards in handling, troublesome product recovery and purification, impossibility of catalyst recycling, etc. In order to avoid these problems, many efforts have been devoted to the research on heterogeneous acid catalysts, which should be safer and environmentally friendly than mineral acids [7][8][9][10][11]. http Owing to some advantages of solid acid catalysts such as high activity, no corrosion, easy handling, and easy to recover and reuse, several types of heterogeneous catalysts have been investigated for acid-catalyzed reactions.…”
Section: Introductionmentioning
confidence: 99%
“…However, these homogeneous catalysts have several drawbacks such as toxic waste, equipment corrosion, hazards in handling, troublesome product recovery and purification, impossibility of catalyst recycling, etc. In order to avoid these problems, many efforts have been devoted to the research on heterogeneous acid catalysts, which should be safer and environmentally friendly than mineral acids [7][8][9][10][11]. http Owing to some advantages of solid acid catalysts such as high activity, no corrosion, easy handling, and easy to recover and reuse, several types of heterogeneous catalysts have been investigated for acid-catalyzed reactions.…”
Section: Introductionmentioning
confidence: 99%
“…From these results, a possible reaction mechanism of the hydroxyalkylation of aromatic hydrocarbons with paraformaldehyde in the presence of ILSO 3 H‐SnCl 5 @Ti‐MCM‐41 is proposed and depicted in Scheme based on our studies and the previous literatures ,,. At first, the paraformaldehyde is depolymerizated by acid catalysis to form formaldehyde„ which can be activated by proton (H+) to form the hydroxymethyl cation (+CH 2 OH).…”
Section: Methodsmentioning
confidence: 65%
“…Ionic liquids (ILs) are well‐known green reaction media and catalysts because of their outstanding and unique properties, and only a few studies were reported in the hydroxyalkylation of aromatics with formaldehyde . Traditionally, these catalytic system have difficulties in separating catalysts from products after the reaction.…”
Section: Methodsmentioning
confidence: 99%
“…184,185 The influence of different ionic liquid media on the addition of hydroxylamine to nitriles was investigated by Voros et al 186 The same research group showed that the application of specific imidazolium, phosphonium and quaternary ammonium based ionic liquids prevented the formation of amide side-product. 187 Tetrabutylphosphonium Brønsted acidic ionic liquids were used to obtain thermoregulated phase-separable reaction systems for the hydroxyalkylation of phenol with formaldehyde to bisphenol F. 188 In the field of biotechnology, a protocol for the enzymatic hydrolysis of rice straw was developed by Yang and Fang. 189 [P 66614 ][C 9 H 19 COO] was used as the solvent during an ultrasound mediated pre-treatment.…”
Section: Preparation and Characterisationmentioning
confidence: 99%